PENGARUH PEMERIKSAAN PAJAK, KESADARAN MEMBAYAR PAJAK, DAN PERSEPSI EFEKTIVITAS SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA KPP PRATAMA DEPOK SAWANGAN) - Emily Ramadania (2021)
This study aims to determine whether there is an effect of tax audits, awareness of paying taxes, and perceptions of the effectiveness of the tax system on taxpayer compliance at KPP Pratama Depok Sawangan. This research uses quantitative with samples are taxpayers who are registered at KPP Pratama Depok Sawangan. Determination of the sample using the Proportionate Stratified Random Sampling technique, that is, the sample will be randomly selected by paying attention to the strata or levels present in the population proportionally where the number of samples in this study is 120 samples. The unit of analysis and population registered at KPP Pratama Depok Sawangan as Corporate Taxpayers and Individual Taxpayers, either Certain Entrepreneurs (WP OP PT) or have an independent business or Employee Individual Taxpayers who have an NPWP. This hypothesis testing uses multiple linear regression with the help of SPSS version 26. So it can be seen that the results of the study are that there is a significant positive effect between all independent variables, namely tax audits, awareness of paying taxes, and perceptions of the effectiveness of the tax system on the dependent variable of taxpayer compliance.